Optoregulated Drug Release from an Engineered Living Material: Self‐Replenishing Drug Depots for Long‐Term, Light‐Regulated Delivery. Issue 5 (27th December 2018) - Sankaran, Shrikrishnan; Becker, Judith; Wittmann, Christoph; del Campo, Aránzazu
Abstract: On‐demand and long‐term delivery of drugs are common requirements in many therapeutic applications, not easy to be solved with available smart polymers for drug encapsulation. This work presents a fundamentally different concept to address such scenarios using a self‐replenishing and optogenetically controlled living material. It consists of a hydrogel containing an active endotoxin‐free Escherichia coli strain. The bacteria are metabolically and optogenetically engineered to secrete the antimicrobial and antitumoral drug deoxyviolacein in a light‐regulated manner. The permeable hydrogel matrix sustains a viable and functional bacterial population and permits diffusion and delivery of the synthesized drug to the surrounding medium at quantities regulated by light dose. Using a focused light beam, the site for synthesis and delivery of the drug can be freely defined. The living material is shown to maintain considerable levels of drug production and release for at least 42 days. These results prove the potential and flexibility that living materials containing engineered bacteria can offer for advanced therapeutic applications. Abstract : A living material for prolonged and light‐controlled drug release . Metabolically and optogenetically engineered Escherichia coli is encapsulated within an agarose‐based hydrogel matrix to produce and release deoxyviolacein, an antimicrobial and antitumoral drug, in response to blue light irradiation. Localized, tunable, and prolonged drug release over 42 days is demonstrated.